Randomized trial of buprenorphine for treatment of concurrent opiate and cocaine dependence - Montoya, Ivan D. (2004)
BACKGROUND: Buprenorphine is a partial μ-opiate agonist and κ-opiate antagonist with established efficacy in the treatment of opiate dependence. Its efficacy for cocaine dependence is uncertain. This study evaluated buprenorphine for the treatment of concomitant cocaine and opiate dependence. METHODS: Two hundred outpatients currently dependent on both cocaine and opiates were randomly assigned to double-blind groups receiving a sublingual solution of buprenorphine (2, 8, or 16 mg daily, or 16 mg on alternate days, or placebo), plus weekly individual drug abuse counseling, for 13 weeks. The chief outcome measures were urine concentrations of opiate and cocaine metabolites (quantitative) and proportion of urine samples positive for opiates or cocaine (qualitative). Group differences were assessed by use of mixed regression modeling. RESULTS: The target dose of buprenorphine was achieved in 179 subjects. Subjects receiving 8 or 16 mg buprenorphine daily showed statistically significant decreases in urine morphine levels (P = .0135 for 8 mg and P < .001 for 16 mg) or benzoylecgonine concentrations (P = .0277 for 8 mg and P = .006 for 16 mg) during the maintenance phase of the study. For the 16-mg group, mean benzoylecgonine concentrations fell from 3715 ng/mL during baseline to 186 ng/mL during the withdrawal phase; mean morphine concentrations fell from 3311 ng/mL during baseline to 263 ng/mL during withdrawal. For the 8-mg group, mean benzoylecgonine concentrations fell from 6761 ng/mL during baseline to 676 ng/mL during withdrawal; mean morphine concentrations fell from 3890 ng/mL during baseline to 661 ng/mL during withdrawal. Qualitative urinalysis showed a similar pattern of results. Subjects receiving the highest dose showed concomitant decreases in both urine morphine and benzoylecgonine concentrations. There were no significant group differences in treatment retention or adverse events. CONCLUSIONS: A sublingual buprenorphine solution at 16 mg daily is well tolerated and effective in reducing concomitant opiate and cocaine use. The therapeutic effect on cocaine use appears independent of that on opiate use.